Evaluating Zakat Fund Governance and Reporting: A PSAK 109-Based Assessment of BAZNAS Indonesia: Evaluasi Tata Kelola dan Pelaporan Dana Zakat: Penilaian Berbasis PSAK 109 terhadap BAZNAS Indonesia - Ifan Ali Alfatani; Muhammad Ibda’u Shulhi (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2025)
The effective governance of Zakat, Infak, and Sedekah (ZIS) funds is crucial for maximizing their socio-economic impact and upholding public trust. This study aims to evaluate the financial reporting and disbursement efficiency of Indonesia's National Board of Zakat (BAZNAS) by analyzing monthly financial statements—a relatively underexplored data source in current literature— from January to October 2024. Utilizing a documentary research approach, which offers a non-intrusive and objective lens, the study assesses key indicators including ZIS receipts, disbursements, program distribution, and alignment with PSAK 109 Revised 2021, the prevailing Islamic accounting standard. Findings reveal a total ZIS receipt of Rp 236.8 billion with an average disbursement ratio of 73.85%, indicating moderate operational efficiency. Social and education programs received the highest allocations, comprising 34.5% and 28.2% respectively, while health and da'wah remained underfunded. However, the study also identifies significant shortcomings in BAZNAS' compliance with PSAK 109, particularly the lack of structured fund classification, omission of fund movement statements, and absence of explanatory notes (Catatan Atas Laporan Keuangan – CALK). These gaps in reporting structure undermine transparency and public accountability. The research contributes to the academic discourse by validating documentary analysis of monthly reports as a credible method for evaluating Islamic nonprofit governance and provides actionable insights for improving zakat financial reporting in alignment with Islamic principles. It also offers practical implications for national zakat institutions and regulators to enhance transparency through digital integration and standardized reporting.